Comparative Assessment of Drone and Knapsack Sprayers for Pod Borer, Helicoverpa armigera (Hubner) Management in Chickpea - D. N. Kambrekar; C. P. Mallapur; P. U. Krishanaraj; Kartik Nidagundi; Naveen; Aruna J; Suresh R. Jambagi (The Indian Journal of Agricultural Sciences, 2026)
The effective management of pod borer, Helicoverpa armigera in chickpea is critical to reducing yield losses. This study evaluates the efficacy of drone-based application of two insecticides, chlorantraniliprole 9.3% + lambda-cyhalothrin 4.6% ZC (200 ml/ha) and emamectin benzoate 5% + lufenuron 40% WG (60 ml/ha), compared to conventional knapsack spraying. Field trials were conducted at the Main Agricultural Research Station, Dharwad, during Rabi 2022-23. Drones applied ultra-low spray volumes (20 l/ha), while knapsack sprayers used 500 l/ha. Larval counts, pod damage, yield, and impact on natural enemies were recorded. Drone application achieved a 100% reduction in larval populations up to 10 days after spraying, compared to 60–80% with knapsack spraying. Pod damage was significantly lower with drones (1.50–2.56%) compared to knapsack sprays (11.48–11.67%). Yield increased to 16.50 q/ha with chlorantraniliprole + lambda-cyhalothrin applied via drones, compared to 10.88 q/ha with knapsack spraying. No phytotoxic effects were observed. Drone application increased larval reduction by 38%, reduced pod damage by 78–87%, and enhanced yield by 31–35%. Despite some reduction in parasitoid populations, drones offer superior pest control and operational efficiency, particularly in labor-scarce areas. This study highlights the potential of drone technology for large-scale, precise, and sustainable pest management in chickpea cultivation. Further research is needed to optimize application rates to balance pest control and conservation of natural enemies.